Epistemologi Pendidikan Islam; Studi Kurikulum SMA MTA Surakarta - Suharto, Toto (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2013)
It is the fact that religious extracurricular learning is done differently and variously by each educational unit level. The interesting phenomenon happens in which is a learning process of religious education extracurricular at a high school of MTA Surakarta. The high school is registered as the list of the fifty leading Islamic high school in Indonesia. This study of educational ideology analyzes is found that at the MTA high school is implemented the integral curriculum structure, that is national curriculum combined with diniyah curriculum . Although it is still in a small portion of the diniyah curriculum made as its core curriculum. The Islamic extracurricular activities are implemented in various forms , such as the recitation on Sunday morning , a special recitation , Arba’in Hadith studies and Riyadlus Shalihin, khitobah , BTA , Tahsin , Tahfidz , Muhadasah, and Tasyji’ul Lughoh and Nafar Ramadan.